Sustained Benefit of 6-Month Topiramate Treatment for Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The effects of discontinuing topiramate after a treatment period of 6 months in 818 patients with migraine, enrolled from 88 clinics in 21 countries in Europe, the UK and Turkey, are reported from University Duisburg-Essen, Germany.